The effects of commodification on cultural significance: two African fortifications - Aggenbach, Adré (School of Architecture, Planning and Geomatics, 2017)
This study is specifically concerned with the impact of cultural tourism on the valorisation of two African fortifications; Castelo São Jorge da Mina (Elmina Castle) in Elmina, Ghana and Casteel de Goede Hoop (Castle of Good Hope) in Cape Town, South Africa. The commodification of national and world heritage, primarily within the context of cultural tourism, is the process by which tangible and intangible heritage are transformed into cultural commodities to be bought, sold and profited from in the heritage and tourism industry. The perception, however, that these commodified heritage sites are contaminated, and less authentic, is based on an outmoded discourse. The South African government has placed a fair amount of focus on redressing highly emotive colonial or dissonant heritage sites with the intent of correcting misinterpreted Eurocentric histories or present non-represented pre-colonial history. The study is structured around addressing the issue of commodification and its impact on the understanding and interpretation of heritage both as an emotive commodity and as a means of providing economic benefit to a community. The literature review locates the research in Marx's theories on commodities together with Urry's tourist gaze. It furthermore includes an analysis on valorisation, with the focus on associative value, in the context of national and world heritage. Fortifications as fortified military architecture in an African context are considered; as is the European influence on African culture and fortifications as colonial structures. Elmina Castle, as a much-researched heritage site, is explored in detail. It includes a legislative analysis; the perspectives and interpretations of the two largest stakeholders groups, the Akan-speaking Fanti population and the African American Diaspora tourists is key to the analysis of the impact of commodification. A detailed history of Europeans on the Gold Coast, the development of Elmina Castle and the impact of trans-Atlantic slavery on the consumption of heritage is studied. The commodification of the Castle of Good Hope is written within the context of the prevailing South African heritage discourse. Much has been written on the commodification of Elmina Castle, while very little has been said about the Castle of Good Hope as a commodity. The prevailing authorised commodification of the Castle of Good Hope necessitated the analysis and comparison of the Castle with the selected comparative case and the study draws comparisons between the powerful emotive significance and contestations attached to Elmina and the contrast that this poses to the Castle of God Hope as a place of heritage significance despite the fact that it has been seen to symbolise the introduction of repressive European influence and control in South Africa. The research supports the notion that cultural tourism and events have impacted on the valorisation of cultural heritage and, in particular, the associative and emotive values. However, the cultural significance of the two African fortifications as important heritage sites are not at risk.